Gender Parity in Riba Literacy: A Comparative Study Among Residents of Sebukar Village - Amanda, Eza; Fauzi, Muhammad; Mursal, Mursal (Cakrawala: Jurnal Studi Islam, 2024)
This study investigates the comparative levels of Riba literacy among male and female residents of Sebukar Village. Employing a quantitative approach, the research utilizes a questionnaire survey administered to 50 males and 50 females. Data analysis is conducted using the Mann-Whitney test to assess significant differences in Riba literacy between genders. Findings reveal no statistically significant disparity in Riba literacy levels between male and female respondents. This research contributes to the existing literature by demonstrating that gender does not appear to be a determining factor in Riba literacy within the specific context of Sebukar Village.